Korupsi Pembebasan Lahan Jalan Jalur Lintas Selatan di Kalurahan Karangawen - Susilo, Erman; R. Widodo Triputro (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Land acquisition corruption in the construction of the Southern Cross Road is a problem that occurs in the Karangawen Village with the main actors being the Lurah for the 2015-2021 period. This problem has an impact on people’s distrust of the village government even though the village head has changed. The research method used is descriptive qualitative with an interpretive approach. Data collection techniques were in the form of observation, documentation, and interviews, with research subjects including officials from the Gunungkidul Regency National Land Agency, Pamong Kalurahan and community leaders from Kalurahan Karangawen. The results of the study found that corruption practices by the former Karangawen Lurah were due to maladministration and abuse of authority. As a result, the public distrust emerged in the village government accompanied by a decrease in development participation even though the village head had changed. Nevertheless, efforts have been made slowly to increase the trust and participation of the community by the lurah and his officials.